2015
DOI: 10.1136/bjophthalmol-2015-306665
|View full text |Cite
|
Sign up to set email alerts
|

Association between the prevalence of obstructive sleep apnoea and the severity of keratoconus

Abstract: Our study revealed that patients with KC are at increased risk of developing OSA, and patients with KC who are at higher risk of developing OSA may have more severe KC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In a large prospective case-control study, 616 patients diagnosed with keratoconus were enroled, along with 616 age, gender and BMI matched controls attending the cornea clinic for refractive errors [103]. Patients had telephone interviews including the Berlin questionnaire.…”
Section: Keratoconusmentioning
confidence: 99%
“…In a large prospective case-control study, 616 patients diagnosed with keratoconus were enroled, along with 616 age, gender and BMI matched controls attending the cornea clinic for refractive errors [103]. Patients had telephone interviews including the Berlin questionnaire.…”
Section: Keratoconusmentioning
confidence: 99%
“…Recent data suggest that SAS may be associated with a number of cardiovascular and cerebrovascular events, such as hypertension (Peppard et al 2000), cardiac arrhythmia (Monahan et al 2009), ischaemic heart disease (Gottlieb et al 2010) and ischaemic stroke (Yaggi et al 2005). Previous studies have demonstrated that SAS is associated with several eye disorders, such as floppy eyelid syndrome (Robert et al 1997), keratoconus (Naderan et al 2015), papilledema (Purvin et al 2000) and optic neuropathy (Mojon et al 1998). Furthermore, an association between glaucoma and SAS has been reported, with the prevalence of SAS being about 20% in patients with primary open-angle glaucoma (POAG) (Mojon et al 2000) and normal-tension glaucoma (NTG) (Mojon et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In a large prospective case control study, 616 patients diagnosed with keratoconus were enrolled, along with 616 age, gender and BMI matched controls attending the cornea clinic for refractive errors (106). Patients had telephone interviews including the Berlin questionnaire.…”
Section: Osamentioning
confidence: 99%